An Analysis of the Relationship between Factors Causing Multi-Drug Resistant Tuberculosis (Mdr-Tb) in the Minahasa Regency Area - Maureen Mamesah; Billy J. Kepel; Nurdjannah Jane Niode (LPPM Universitas Harapan Bangsa, 2024)
The World Health Organization (WHO) estimates that only 8.5% of multidrug-resistant tuberculosis (MDR-TB) is successfully treated. This study analyzes the factors contributing to Multi-Drug Tuberculosis Resistance in Minahasa Regency. This research uses mixed methods that combine quantitative and qualitative methods. Quantitative data uses a cross-sectional study approach, while qualitative in-depth interview data is the basis for strengthening quantitative data. The research was conducted from April to May 2024 in three districts in Minahasa: Tompaso, Kawangkoan, and Langowan. This study involved 111 respondents (94 people with pulmonary TB and 17 people with MDR-TB) and six key informants (4 from the patient's family and two health workers). The results showed that the incidence of MDR-TB in TB sufferers was significantly related to age ≤40 years (p=0.016), marital status (p=0.011), and adherence to taking medication (p=0.000). Multivariate analysis showed a significant relationship simultaneously between age, marital status, and medication adherence and the incidence of MDR-TB, with a p-value of 0.000 (OR 5.529). These results were strengthened by key informants who explained that sufferers experienced difficulties in complying with treatment due to complaints of OAT side effects and the large variety of drugs. In conclusion, there is a significant relationship between age, marital status, adherence to taking medication, and the incidence of MDR TB in Minahasa Regency